The Choice of Governance Modes in LSPs Foreign Operations - Lemoine, Olga W. (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
Different theoretical approaches have been used to understand the choice between alternative modes of governance. Transaction cost (TC), resource based (RB), and the “Nordic” paradigms offer different but somewhat complementary explanations to the problem. These theories have been used in a wide range of empirical studies. Most of them have centered their attention on manufacturing firms, and quite a few have focused on the service sector. Almost no interest has been shown in the analysis of the factors affecting the LSPs selection of governance models to perform foreign operations. With the interest in filling this gap, this paper focuses on the identification of the main variables or factors able to explain LSPs modal choice in international markets. The analysis was done using an eclectic-syncretic paradigm, which combines the main trends within TC and RB theories. 11 main factors or variables able to explain modal choice in foreign operations were found. A set of general and specific hypotheses for each variable was developed.